Sequential cross-linking based sea fennel composite intelligent microcapsules, preparation method and application thereof

CN122376463BActive Publication Date: 2026-10-20CHANGCHUN UNIV OF CHINESE MEDICINE +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610837414.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-10-20
Estimated Expiration
2046-06-11

AI Technical Summary

Technical Problem

[0004]本发明为针对海茴香提取物化学不稳定、透皮率低、缺乏环境响应性,以及现有微囊化技术囊壁结构松散、无法精准调控的问题,提供了基于顺序交联的海茴香复合智能微囊及制备方法和应用

Benefits of technology

[0015]与现有技术相比,本发明的有益效果是:本发明通过整合微流控辅助逐层自组装、等温滴定量热法实时监控交联反应、原子力显微镜-纳米压痕单颗粒机械性能表征等具有高可控性和独特性的制备与表征技术,并创新性地采用“离子交联-功能化修饰-共价加固”三步顺序交联机制,成功构建了一种结构均一性高、机械性能卓越、具有精准pH响应阈值的智能微囊系统,实现了对活性物的温和高效包封、对皮肤屏障状态的主动感知与精准释放控制,以及微囊机械强度与加工耐受性的协同增强,为高端功能性化妆品开发提供了具有高技术壁垒的载体解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122376463B_ABST
    Figure CN122376463B_ABST
Patent Text Reader

Abstract

The application discloses a sea fennel composite intelligent microcapsule based on sequential cross-linking, a preparation method and application, and belongs to the technical field of biomedicine.The application provides the sea fennel composite intelligent microcapsule based on sequential cross-linking, aiming at the problems of chemical instability, low transdermal rate, lack of environmental responsiveness of sea fennel extract, and loose capsule wall structure of existing microencapsulation technology, and incapability of precise control.Through integration of high-controllable technologies such as microfluidic layer-by-layer self-assembly, isothermal titration calorimetry monitoring cross-linking and atomic force microscope-nano indentation characterization, three-step sequential cross-linking is adopted to construct the intelligent microcapsule which is uniform in structure, excellent in mechanical performance, has a precise pH response threshold, realizes mild and efficient encapsulation of active substances, actively senses the skin barrier state and precisely controls the release, and synergistically enhances the mechanical strength and processing resistance, thereby providing a carrier solution with high technical barriers for high-end functional cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical technology, and in particular relates to a sea fennel composite smart microcapsule based on sequential cross-linking, its preparation method, and its application. Background Technology

[0002] The phenolic acids, chlorogenic acid, and flavonoids in sea fennel possess the ability to resist extreme environments such as high salt and high UV radiation, and can quickly repair damaged areas, promoting cell and tissue regeneration. Therefore, this plant extract helps rebuild the human dermis and enhances its barrier function, making it a safe and effective natural anti-pollution cosmetic ingredient. As the cosmetic industry moves towards higher efficiency and precision, plant extracts with excellent repair and anti-aging activities, such as sea fennel extract (CSE), have become a research hotspot. However, sea fennel itself suffers from poor chemical stability, low transdermal penetration, and difficulty responding to complex skin microenvironments, severely limiting its efficacy. Furthermore, most commercially available sea fennel is in freeze-dried powder form, insoluble in both oil and water, further restricting its application in the cosmetic field.

[0003] Therefore, developing an intelligent carrier system that can actively sense skin condition and precisely release nutrients is key to overcoming current technological bottlenecks. However, existing microencapsulation technologies mostly rely on simple single-step mixing or conventional cross-linking methods, resulting in relatively loose capsule wall structures with limited protection for active ingredients and difficulty in responding to complex physiological microenvironment changes. In particular, there is currently a lack of finely tunable processes for constructing intelligent carriers with precise sequence structures and well-defined stimulus response thresholds. Summary of the Invention

[0004] This invention addresses the problems of chemical instability, low transdermal penetration, and lack of environmental responsiveness of sea fennel extract, as well as the loose capsule wall structure and inability to precisely control existing microencapsulation technologies. It provides a sea fennel composite intelligent microcapsule based on sequential cross-linking, its preparation method, and its application.

[0005] One objective of this invention is to provide a method for preparing sea fennel composite intelligent microcapsules based on sequential cross-linking, the preparation method comprising the following steps: S1: Weigh out sea fennel extract CSE and dissolve it in lactate-sodium lactate buffer solution at pH 4.80. Vortex the solution until it is completely dissolved. Filter the solution through a 0.22 μm aqueous filter membrane to obtain CSE stock solution. Store at 4°C in the dark. S2: Weigh carboxymethyl chitosan and dissolve it in a lactate-sodium lactate buffer solution at pH 5.20. Stir overnight until completely dissolved to obtain a carboxymethyl chitosan solution. Weigh sodium tripolyphosphate and dissolve it in deionized water. Stir at 800 rpm to obtain a sodium tripolyphosphate solution. Add the sodium tripolyphosphate solution dropwise to the carboxymethyl chitosan solution at a rate of 1 mL / min. Continue stirring for 30 min to carry out the pre-crosslinking reaction. Finally, make up the volume with a lactate-sodium lactate buffer solution at pH 5.20 and filter through a 0.45 μm filter membrane to obtain a pre-crosslinking solution containing carboxymethyl chitosan and sodium tripolyphosphate. S3: The CSE stock solution prepared in S1 is used as phase A, and the pre-crosslinked solution prepared in S2 is used as phase B. The phase A and phase B solutions are respectively loaded into two independent syringes with precision injection pumps. The phase A and phase B solutions are introduced into the Inlet A and Inlet B of the microfluidic chip through polytetrafluoroethylene tubes, respectively. Under laminar flow conditions, the fluid turns multiple times through the serpentine channel and achieves gentle layer-by-layer encapsulation by interfacial diffusion. The opalescent suspension is collected from the microfluidic chip outlet and aged at 25°C for 30 min to obtain the primary microcapsule suspension. S4: Under magnetic stirring conditions of 25 ± 1°C and 500 rpm, the LA stock solution was added dropwise to the primary microcapsule suspension prepared in S3. After the addition was completed, stirring was continued for 30 min to obtain the LA-functionalized microcapsule suspension. S5: Place the LA-functionalized microcapsule suspension from S4 into an ITC sample cell, heat it to 45°C, and titrate the SGE working solution under continuous stirring and ITC monitoring until the system heat flow signal stabilizes and returns to the baseline, indicating that the covalent cross-linking reaction is nearing completion, and obtain sea fennel composite intelligent microcapsules.

[0006] In a preferred embodiment of the present invention, the preparation method of the lactate-sodium lactate buffer solution in S1 is as follows: weigh 0.42 g of lactic acid and 0.58 g of sodium lactate, dissolve them in 100 mL of deionized water, and adjust the pH to 4.80.

[0007] In a preferred embodiment of the present invention, the concentration of the CSE stock solution in S1 is 1.0% (w / v).

[0008] In a preferred embodiment of the present invention, the mass-to-volume ratio of the sea fennel extract to the lactate-sodium lactate buffer solution in S1 is 10 mg: 1 mL.

[0009] In a preferred embodiment of the present invention, the concentration of the carboxymethyl chitosan solution in S2 is 3.0%; the concentration of the sodium tripolyphosphate solution is 0.3%; and the mass ratio of the sodium tripolyphosphate to the carboxymethyl chitosan is 1:10.

[0010] In a preferred embodiment of the present invention, the flow rates of phase A and phase B solutions introduced into the microfluidic chip via polytetrafluoroethylene tubes in S3 are 15 μL / min and 10 μL / min, respectively.

[0011] In a preferred embodiment of the present invention, the preparation method of the LA stock solution in S4 is as follows: 3.00 g of lactobionic acid is weighed and dissolved in 10 mL of lactate-sodium lactate buffer solution with pH 4.80, and dissolved by vortexing to obtain an LA stock solution with a concentration of 30% (w / v); the mixing volume ratio of the primary microcapsule suspension to the LA stock solution is 143:1.

[0012] In a preferred embodiment of the present invention, the preparation method of the SGE working solution in S5 is as follows: Take 200 μL of 3-glycidyl ether oxypropyltrimethoxysilane stock solution, add 800 μL of anhydrous ethanol and 100 μL of 0.1 M hydrochloric acid, vortex mix, and let stand at room temperature for hydrolysis for 30 min; then, dilute it with lactate-sodium lactate buffer solution at pH 4.80 and make up to 10 mL to obtain an SGE working solution with a concentration of 20 mM. This solution should be prepared fresh for use.

[0013] The second objective of this invention is to provide a sea fennel composite intelligent microcapsule based on sequential cross-linking, wherein the sea fennel composite intelligent microcapsule is obtained by the above-described preparation method.

[0014] The third objective of this invention is to provide the application of the above-mentioned sea fennel composite intelligent microcapsules in the preparation of tissue repair materials, regenerative medicine materials or cosmetics.

[0015] Compared with existing technologies, the beneficial effects of this invention are as follows: This invention integrates highly controllable and unique preparation and characterization technologies such as microfluidic-assisted layer-by-layer self-assembly, isothermal titration calorimetry for real-time monitoring of cross-linking reactions, and atomic force microscopy-nanoplastin single-particle mechanical property characterization. It also innovatively adopts a three-step sequential cross-linking mechanism of "ionic cross-linking-functionalization modification-covalent reinforcement" to successfully construct an intelligent microcapsule system with high structural uniformity, excellent mechanical properties, and precise pH response threshold. This achieves gentle and efficient encapsulation of active ingredients, active sensing and precise release control of skin barrier status, and synergistic enhancement of microcapsule mechanical strength and processing tolerance, providing a carrier solution with high technical barriers for the development of high-end functional cosmetics.

[0016] The core innovation of this invention lies in the introduction and integration of a series of highly controllable and unique preparation and characterization techniques to construct a smart microcapsule capable of actively sensing and responding to skin barrier state (pH changes). Specifically, this includes: 1) A microfluidic-assisted layer-by-layer self-assembly (LbL) strategy: Through precise laminar flow control within microchannels, the active ingredient is gently and layer-by-layer encapsulated at the liquid interface, overcoming the shear damage and uneven mixing problems that may occur with traditional stirring and mixing, thereby significantly improving the structural uniformity, encapsulation efficiency, and batch repeatability of the microcapsules. 2) Real-time monitoring and optimization of the crosslinking reaction process using isothermal titration calorimetry: By real-time monitoring of the reaction heat signal, the stoichiometric endpoint of the crosslinking agent addition and the degree of reaction completion are accurately determined, breaking through the limitations of traditional empirical time control. This achieves visualized and quantitatively precise control of the crosslinking process, ensuring the complete formation and structural stability of the crosslinked network. 3) Quantitative characterization of single-particle mechanical properties using atomic force microscopy-nanoindentation technology: The elastic modulus and deformation behavior of individual microcapsules are directly measured at the nanoscale, overcoming the limitation that macroscopic rheological tests can only reflect the average response of the microcapsule population. This provides direct and reliable experimental evidence for the accurate evaluation of the mechanical strength of smart carriers, process optimization, and performance correlation.

[0017] This invention utilizes a sequential crosslinking mechanism to construct a microcapsule network through three steps, achieving intelligent response and structural enhancement: (1) Ionic crosslinking: The carboxyl groups of carboxymethyl chitosan (CMCS) and sodium tripolyphosphate (TPP) polyvalent anions form a primary ionic network through electrostatic interaction, providing basic encapsulation and skeleton stability. (2) Functional modification: The carboxyl groups of lactobionic acid (LA) form hydrogen bonds with the amino / hydroxyl groups of CMCS, giving it pH responsiveness - the network shrinks when pH < 5.8, and deprotonates at pH ≈ 6.8 to generate negative charge repulsion, causing the network to swell and achieving "intelligent gating" release. (3) Covalent reinforcement: The epoxy groups of SGE undergo ring-opening addition with the amino / hydroxyl groups of CMCS / LA to form ether bonds, while the silane groups hydrolyze and condense to form siloxane bonds, constructing a three-dimensional covalent network, which significantly improves the mechanical strength and processing tolerance of the microcapsules. This sequential strategy achieves programmable structure construction, precise control of pH response threshold, and synergistic enhancement of mechanical properties through stepwise bonding of "ionic bonds-hydrogen bonds-covalent bonds," which is significantly different from traditional single crosslinking or simple blending processes.

[0018] Based on the integrated application of the above technologies, this invention ensures that the final product, sea fennel extract intelligent microcapsules (SM-CSE), has the following advantages: (1) Enhanced intelligent responsiveness: The release rate of SM-CSE at pH 6.8 is 2.45 times higher than that at pH 5.5, demonstrating microenvironment-responsive release capability. (2) Enhanced mechanical properties: Sequential cross-linking results in an elastic modulus of 85.6 MPa for the microcapsules, which is 3-4 times that of traditional microcapsules, making the structure more stable and the processing tolerance better. (3) Clear barrier repair effect: SM-CSE can significantly enhance the expression of Filaggrin and Loricrin, reduce ROS levels, and promote epidermal repair, with better effects than CSE. (4) High process controllability: By adopting microfluidics, ITC, AFM and other technologies, the controllable preparation of microcapsule structure and precise regulation of performance are achieved.

[0019] In summary, the sea fennel composite intelligent microcapsules constructed in this invention have clear advantages in terms of responsive release, structural stability, and enhanced bioactivity, providing a feasible path for the development of intelligent responsive cosmetic carriers and offering a novel carrier solution with high technical barriers for the development of high-end functional cosmetics. Attached Figure Description

[0020] Figure 1 The first section is a bar chart showing the effect of different TPP concentrations on the encapsulation efficiency (using 0.1% BSA as a model) under the optimal CMCS concentration conditions; the second section is a bar chart showing the effect of different TPP concentrations on the primary microcapsule particle size. Figure 2 Microcapsules with different LA loadings were tested at 1720 cm⁻¹ -1 A statistical chart of the relative peak areas of the characteristic C=O peaks; ±s, n=3; Figure 3 A bar chart showing the effect of different LA loadings (2%-10%) on the zeta potential of microcapsules; Figure 4 Bar chart comparing the cumulative release rates of microcapsules with different LA loadings over 36 hours at different pH values; A represents pH 5.5, and B represents pH 6.8. Figure 5 Transmission electron microscopy (TEM) images of SM-CSE; Figure 6 Full FTIR spectra of SM, SM-CSE, MC-CL, and MC-CT (4000-500 cm⁻¹) -1 ); Figure 7 A bar chart showing the particle size comparison of SM-CSE, MC-CL, and MC-CT under pH 5.5 and pH 6.8 conditions; Figure 8A bar chart comparing the zeta potentials of SM-CSE, MC-CL, and MC-CT at pH 5.5 and pH 6.8. Figure 9 A continuous curve of SM-CSE particle size versus pH obtained by environmental control-DLS coupled measurement; pH 4.5-7.5; Figure 10 Line graph showing the FRET efficiency changes of SM-CSE under different pH conditions; Figure 11 A bar chart comparing the elastic moduli of SM-CSE, MC-CL, and MC-CT; Figure 12 A bar chart comparing the deformation rates of SM-CSE, MC-CL, and MC-CT; Figure 13 Line graph showing the effect of different pressure treatments on the release rates of SM-CSE, MC-CL, and MC-CT; Figure 14 Bar chart comparing the storage modulus (G') of SM-CSE, MC-CL, and MC-CT suspensions; Figure 15 The curves show the changes in the cumulative release rate of SM-CSE in vitro under pH 5.5 and pH 6.8 conditions; Figure 16 The curves showing the changes in the cumulative release rate of MC-CL in vitro under pH 5.5 and pH 6.8 conditions; Figure 17 The curves show the changes in the cumulative release rate of MC-CT in vitro under pH 5.5 and pH 6.8 conditions; Figure 18 A bar chart comparing the 24-hour cumulative transdermal dose of CSE, MC-CL, MC-CT, and SM-CSE; Figure 19 A bar chart comparing 24-hour skin retention for CSE, MC-CL, MC-CT, and SM-CSE; Figure 20 A bar chart showing the relative viability (%) of HaCaT cells in different treatment groups; Figure 21 A bar chart showing the relative ROS levels (%) in HaCaT cells from different treatment groups; Figure 22 A bar chart showing the relative expression levels of Filaggrin protein in different treatment groups during in vitro cell experiments; Figure 23 A bar chart showing the relative expression levels of Loricrin protein in different treatment groups during in vitro cell experiments; Figure 24Representative photographs of the skin on the back of rats in different treatment groups on day 7 of treatment; Figure 25 A graph showing the change in skin damage score over time (days 0, 3, and 7); Figure 26 Quantitative statistical bar chart of epidermal thickness for different treatment groups; Figure 27 Bar chart showing the relative expression levels of Filaggrin protein in different treatment groups in animal experiments; Figure 28 A bar chart showing the relative expression levels of Loricrin protein in different treatment groups during animal experiments. Detailed Implementation

[0021] Those skilled in the art can refer to the content of this document and appropriately improve the process parameters to achieve the desired results. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments, and those skilled in the art can obviously make modifications or appropriate alterations and combinations to the methods and applications described herein without departing from the content and scope of this invention to implement and apply the technology of this invention.

[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0023] Example 1: Single-factor optimization of CMCS concentration and TPP crosslinking degree 0.5 g, 1.0 g, 1.5 g, 2.0 g, and 3.0 g of carboxymethyl chitosan (CMCS, Mw≈150 kDa, degree of carboxylation≥80%) were weighed and dissolved in 100 mL of lactate-sodium lactate buffer solution at pH 5.20. The CMCS was completely dissolved by magnetic stirring. The resulting solution was filtered through a 0.45 μm microporous membrane to remove impurities, and CMCS solutions with concentrations of 0.5%, 1.0%, 1.5%, 2.0%, and 3.0% (w / v) were obtained, respectively, and stored at 4℃ for later use. 0.1 g, 0.2 g, 0.3 g, 0.4 g, and 0.5 g of sodium tripolyphosphate (TPP) were weighed and dissolved in 100 mL of deionized water. TPP solutions with concentrations of 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% (w / v) were obtained by magnetic stirring at 800 rpm. The TPP solution was added dropwise to an equal volume of CMCS solution under magnetic stirring at 500 rpm, and the changes in the state of the system were observed. Evaluation indicators included: physical stability (state after 24 hours of standing); dynamic light scattering (DLS) to determine particle size and polydispersity index (PDI); and preliminary encapsulation experiments using bovine serum albumin (BSA) as a model drug.

[0024] The results are shown in Table 1. When the concentration of CMCS is ≥2.0% and the concentration of TPP is ≥0.2%, the system begins to show opalescence. When the concentration of CMCS is 3.0% (w / v) and the concentration of TPP is 0.3% (w / v), the prepared suspension has the most uniform and delicate opalescence. After standing for 24 hours, the suspension showed no obvious precipitation or stratification.

[0025] The results are shown in Table 2 and Figure 1 As shown, as the TPP concentration increased from 0.1% to 0.3%, the size of the primary microcapsules decreased from 320 nm to 200 nm, while the BSA encapsulation efficiency increased from 45% to 65%. When the TPP concentration continued to increase to 0.4% and 0.5%, the particle size change was not significant, but slight flocculation occurred in the system, and the encapsulation efficiency decreased. Therefore, this invention determined that the optimal mass ratio of CMCS to TPP is 10:1 (i.e., 3.0%:0.3%), with an average particle size of 199.7±10.1 nm, a polydispersity index of 0.14±0.02, and a BSA encapsulation efficiency of 64.8±2.5%. At this ratio, the pre-crosslinked network structure formed is stable and has high encapsulation efficiency.

[0026] Table 1

[0027] Table 2

[0028] Example 2: Preparation of primary microcapsule suspension S1: Weigh 100.0 mg of sea fennel extract (CSE) and dissolve it in 10 mL of lactate-sodium lactate buffer solution at pH 4.80 (weigh 0.42 g of lactic acid and 0.58 g of sodium lactate, dissolve them in 100 mL of deionized water, and adjust the pH to 4.80). Vortex the solution until completely dissolved, filter it through a 0.22 μm aqueous filter membrane to obtain a 1.0% (w / v) CSE stock solution, and store it at 4°C protected from light. S2: Weigh 3.0 g of carboxymethyl chitosan (CMCS) and dissolve it in 100 mL of lactate-sodium lactate buffer solution at pH 5.20. Stir overnight until completely dissolved to obtain a CMCS solution with a concentration of 3.0% (w / v). Weigh 0.3 g of sodium tripolyphosphate (TPP) and dissolve it in 100 mL of deionized water. Stir at 800 rpm to obtain a TPP solution with a concentration of 0.3% (w / v). Add the sodium tripolyphosphate solution dropwise to the carboxymethyl chitosan solution at a rate of 1 mL / min and continue stirring for 30 min to carry out the pre-crosslinking reaction. Finally, make up the volume with lactate-sodium lactate buffer solution at pH 5.20 and filter through a 0.45 μm filter membrane to obtain a pre-crosslinking solution containing CMCS and TPP. S3: The CSE stock solution prepared in S1 is used as phase A, and the pre-crosslinked solution prepared in S2 is used as phase B. The phase A and phase B solutions are respectively loaded into two independent syringes with precision injection pumps. The phase A and phase B solutions are introduced into the Inlet A and Inlet B of the microfluidic chip through polytetrafluoroethylene tubes at flow rates of 15 μL / min and 10 μL / min, respectively. Under laminar flow conditions, the fluid turns multiple times through the serpentine channel and achieves gentle layer-by-layer encapsulation by interfacial diffusion. The opalescent suspension is collected from the outlet of the microfluidic chip and aged at 25°C for 30 min to obtain the primary microcapsule suspension (abbreviated as: MC-P suspension).

[0029] Example 3: Single-factor optimization of LA stock solution concentration Weigh 3.00 g of lactobionic acid (LA), dissolve it in 10 mL of lactate-sodium lactate buffer solution at pH 4.80, and vortex to dissolve it, to obtain a stock solution of LA with a concentration of 300 mg / mL (30%, w / v).

[0030] Six portions of the MC-P suspension prepared in Example 2 were accurately measured, each with a volume of 3.33 mL (calculated based on the CMCS concentration in MC-P, ensuring that the CMCS matrix mass in each sample was 100 mg), and placed in six clean 10 mL sample cells. The mass loading ratio of LA to CMCS was set at a gradient of 2%, 4%, 6%, 7%, 8%, and 10%, with three parallel samples (n=3) for each gradient.

[0031] Taking the 7% loading group as an example, the calculation process for the amount of LA stock solution to be added is as follows: the required LA mass is 100 mg × 7% = 7 mg; the corresponding volume of LA stock solution to be added is: 7 mg ÷ 300 mg / mL (LA stock solution concentration) = 23.3 μL; in actual operation, in order to improve the sampling accuracy, the LA stock solution is diluted 10 times with pH 4.80 buffer before use, and the volume of LA stock solution to be added is 233 μL.

[0032] Each sample was prepared by adding the calculated LA stock solution dropwise to the 6 MC-P suspensions prepared in Example 2 under magnetic stirring conditions of 25±1°C and 500 rpm. After the addition was completed, the mixture was stirred for another 30 min, and then the subsequent performance characterization was carried out immediately.

[0033] The optimal loading was evaluated using a multi-index approach: physical indicators (measurement of zeta potential changes), functional indicators (evaluation of pH responsiveness: determination of critical swelling pH through pH-dependent particle size changes), and in vitro release behavior (comparison of sustained-release performance at pH 5.5 with release rate and release factor at pH 6.8).

[0034] like Figure 2 As shown, as the LA loading increased from 2% to 10%, the microcapsules at 1720 cm⁻¹... -1 The significant increase in the relative peak area of ​​the C=O characteristic peak indicates that LA was successfully incorporated into the microcapsule structure, and the amount of incorporation increased with the increase of loading.

[0035] like Figure 3 As shown, with the increase of LA loading, the negative value of the microcapsule Zeta potential gradually increases, from -20 mV (2% loading) to -38 mV (10% loading), further confirming the increase in the number of carboxyl groups on the microcapsule surface.

[0036] like Figure 4 As shown in Table 3, the microcapsules exhibited the most ideal smart release characteristics when the LA loading was 7%: the release was slowest at pH 5.5 (28.7%) and fastest at pH 6.8 (70.2%), with the release rate increasing by a factor of 2.45 to the maximum. Below 7% loading, pH responsiveness was insufficient; above 7%, the sustained-release performance at pH 5.5 decreased. Therefore, the optimal LA loading was determined to be 7% (w / w, relative to CMCS).

[0037] Table 3

[0038] Example 4: Preparation of a Sea Fennel Composite Smart Microcapsule Based on Sequential Crosslinking Under magnetic stirring conditions at 25°C and 500 rpm, the LA stock solution prepared in Example 3 was added dropwise to the primary microcapsule suspension prepared in Example 2 at a mixing volume ratio of 143:1. After the addition was completed, stirring was continued for 30 min to obtain the LA-functionalized microcapsule suspension. The LA-functionalized microcapsule suspension was placed in an ITC sample cell and heated to 45°C. Under continuous stirring and monitoring by ITC, the SGE working solution was titrated according to a preset program (2 μL injected each time, 180 s interval). The preparation steps were as follows: 200 μL of 3-glycidyl ether oxypropyltrimethoxysilane stock solution was added to 800 μL of anhydrous ethanol and 100 μL of 0.1 M hydrochloric acid, vortexed, and allowed to stand at room temperature for hydrolysis for 30 min; then diluted with lactate-sodium lactate buffer at pH 4.80 and brought to a final volume of 10 mL to obtain a 20 mM SGE working solution. This solution should be prepared fresh before use. The titration continued until the system heat flow signal stabilized and returned to the baseline, indicating that the covalent cross-linking reaction was nearing completion, and sea fennel composite intelligent microcapsules (abbreviated as: SM-CSE) were obtained.

[0039] Comparative Example 1: S1: Weigh 100.0 mg of sea fennel extract (CSE) and dissolve it in 10 mL of lactate-sodium lactate buffer solution at pH 4.80 (weigh 0.42 g of lactic acid and 0.58 g of sodium lactate, dissolve them in 100 mL of deionized water, and adjust the pH to 4.80). Vortex the solution until completely dissolved, filter it through a 0.22 μm aqueous filter membrane to obtain a 1.0% (w / v) CSE stock solution, and store it at 4°C protected from light. S2: Weigh 3.0 g of carboxymethyl chitosan (CMCS) and dissolve it in 100 mL of lactate-sodium lactate buffer solution at pH 5.20. Stir overnight until completely dissolved to obtain a CMCS solution with a concentration of 3.0% (w / v). Weigh 0.3 g of sodium tripolyphosphate (TPP) and dissolve it in 100 mL of deionized water. Stir at 800 rpm to obtain a TPP solution with a concentration of 0.3% (w / v). Add the sodium tripolyphosphate solution dropwise to the carboxymethyl chitosan solution at a rate of 1 mL / min and continue stirring for 30 min to carry out the pre-crosslinking reaction. Finally, make up the volume with lactate-sodium lactate buffer solution at pH 5.20 and filter through a 0.45 μm filter membrane to obtain a pre-crosslinking solution containing CMCS and TPP. S3: Use the CSE stock solution prepared in S1 as phase A and the pre-crosslinked solution prepared in S2 as phase B; take 10 mL of phase A (1.0% CSE, pH 4.80 buffer) and place it in a 50 mL beaker, and stir continuously at 800 rpm on a magnetic stirrer; use a syringe pump to add 10 mL of phase B (pre-crosslinked solution of 3.0% CMCS and 0.3% TPP, pH 5.20) dropwise to phase A at a rate of 1 mL / min; after the addition is complete, continue stirring for 30 min, and then let it stand at room temperature for 30 min to age, thus obtaining the microcapsules prepared by the conventional stirring method (abbreviated as: MC-CL).

[0040] Comparative Example 2: S1: Weigh 100.0 mg of sea fennel extract (CSE) and dissolve it in 10 mL of lactate-sodium lactate buffer solution at pH 4.80 (weigh 0.42 g of lactic acid and 0.58 g of sodium lactate, dissolve them in 100 mL of deionized water, and adjust the pH to 4.80). Vortex the solution until completely dissolved, filter it through a 0.22 μm aqueous filter membrane to obtain a 1.0% (w / v) CSE stock solution, and store it at 4°C protected from light. S2: Weigh 3.0 g of carboxymethyl chitosan (CMCS) and dissolve it in 100 mL of lactate-sodium lactate buffer solution at pH 5.20. Stir overnight until completely dissolved to obtain a CMCS solution with a concentration of 3.0% (w / v). Weigh 0.3 g of sodium tripolyphosphate (TPP) and dissolve it in 100 mL of deionized water. Stir at 800 rpm to obtain a TPP solution with a concentration of 0.3% (w / v). Add the sodium tripolyphosphate solution dropwise to the carboxymethyl chitosan solution at a rate of 1 mL / min and continue stirring for 30 min to carry out the pre-crosslinking reaction. Finally, make up the volume with lactate-sodium lactate buffer solution at pH 5.20 and filter through a 0.45 μm filter membrane to obtain a pre-crosslinking solution containing CMCS and TPP. S3: Using the CSE stock solution prepared in S1 as phase A and the pre-crosslinked solution prepared in S2 as phase B; take 10 mL of phase A (1.0% CSE, pH 4.80 buffer) and place it in a 50 mL beaker. Under continuous stirring at 500 rpm on a magnetic stirrer, directly add the calculated amount of LA (7% of the CMCS mass) and excess SGE (KH-560, final concentration 5 mM) to the microcapsule suspension. Heat the reaction system to 45℃ and stir continuously for 2 hours to complete the covalent crosslinking, thus obtaining conventional co-crosslinked microcapsules (abbreviated as: MC-CT).

[0041] Comparative Example 3: S1: Take 10 mL of pH 4.80 lactate-sodium lactate buffer (weigh 0.42 g lactate and 0.58 g sodium lactate, dissolve in 100 mL deionized water, and adjust the pH to 4.80) as phase A, filter through a 0.22 μm aqueous filter membrane, and store at 4℃ in the dark for later use. S2: Weigh 3.0 g of carboxymethyl chitosan (CMCS) and dissolve it in 100 mL of lactate-sodium lactate buffer solution at pH 5.20. Stir overnight until completely dissolved to obtain a CMCS solution with a concentration of 3.0% (w / v). Weigh 0.3 g of sodium tripolyphosphate (TPP) and dissolve it in 100 mL of deionized water. Stir at 800 rpm to obtain a TPP solution with a concentration of 0.3% (w / v). Add the sodium tripolyphosphate solution dropwise to the carboxymethyl chitosan solution at a rate of 1 mL / min and continue stirring for 30 min to carry out the pre-crosslinking reaction. Finally, make up the volume with lactate-sodium lactate buffer solution at pH 5.20 and filter through a 0.45 μm filter membrane to obtain a pre-crosslinking solution containing CMCS and TPP. S3: Using the blank buffer solution prepared in S1 as phase A and the pre-crosslinked solution prepared in S2 as phase B; take 10 mL of phase A (pH 4.80 buffer solution) and place it in a 50 mL beaker. Under continuous stirring at 500 rpm on a magnetic stirrer, directly add the calculated amount of LA (7% of the CMCS mass) and excess SGE (KH-560, final concentration 5 mM) to the blank solution. Heat the reaction system to 45℃ and stir continuously for 2 hours to complete the covalent crosslinking, thus obtaining the empty-loaded conventional mixed microcapsules (abbreviated as: SM).

[0042] Effect Experiment: 1. Performance characterization of smart microcapsules (1) Transmission electron microscopy (TEM) analysis Transmission electron microscopy (TEM) analysis was performed on the sea fennel composite intelligent microcapsules (SM-CSE) prepared in Example 4, and the results are as follows: Figure 5 As shown in the TEM image, SM-CSE is a regular sphere with a clear core-shell structure; the average particle size of 50 microcapsules is 185.3±8.7 nm and the shell thickness is 24.5±2.1 nm.

[0043] (2) Fourier transform infrared spectroscopy (FTIR) analysis The microcapsule samples prepared in Example 4 (SM-CSE), Comparative Example 1 (MC-CL), Comparative Example 2 (MC-CT), and Comparative Example 3 (SM) were freeze-dried and then ground. One mg of the dried sample powder was taken from each sample and thoroughly mixed with approximately 100 mg of spectroscopically pure potassium bromide (KBr) in an agate mortar and ground until homogeneous. The mixture was then pressed into transparent sheets and subjected to Fourier transform infrared spectroscopy at 4000-500 cm⁻¹. -1 Scanning analysis was performed within the wavenumber range.

[0044] like Figure 6 As shown, the SM-CSE spectrum is at 1720 cm⁻¹. -1A characteristic peak for the C=O group of the LA carboxyl group appears nearby, at 1635 cm⁻¹. -1 and 1550 cm -1 A new peak appears in the vicinity of the amide I / II band, and a broad peak of -OH (3400 cm⁻¹) is observed. -1 The relative weakening of the crosslinking effect; these changes verify that the sequential crosslinking process of "CMCS-TPP ionic crosslinking → LA carboxyl binding → SGE covalent crosslinking" has successfully occurred; the MC-CL and MC-CT spectra are basically consistent with the SM spectra, and no obvious new characteristic peaks are observed.

[0045] (3) Characterization of pH response behavior Environmentally controlled dynamic light scattering test: 1 mL of each microcapsule suspension (concentration 2 mg / mL) prepared in Example 4 (SM-CSE), Comparative Example 1 (MC-CL), and Comparative Example 2 (MC-CT) was placed in the DLS sample cell; 0.1 M potassium hydroxide solution (preparation steps: accurately weigh 0.56 g KOH, dissolve and dilute to 100 mL deionized water) was used as the titrant, and the pH of the system was continuously changed by the environmental control unit, while the change of microcapsule hydrodynamic particle size with pH was monitored simultaneously.

[0046] As shown in Table 4, Figure 7-8 As shown, compared to pH 5.5, the particle size of SM-CSE increased significantly (by ~40%) at pH 6.8, and the negative value of the Zeta potential increased significantly; while the particle size and potential of the microcapsules prepared by Comparative Example 1 (MC-CL) and Comparative Example 2 (MC-CT) did not change significantly; this indicates that the network structure of SM-CSE has significant pH-dependent swelling characteristics.

[0047] like Figure 9 As shown, when pH < 5.8, the microcapsule particle size prepared in Example 4 remained stable at approximately 180 nm; after pH > 5.8, the particle size began to increase significantly; the inflection point at which the particle size began to increase sharply was defined as the critical swelling pH (pH). t The value was 5.82 ± 0.05.

[0048] Table 4

[0049] Note: p < 0.01 compared to data for the same sample at pH 5.5.

[0050] (4) FRET probe method: 1) Labeling and purification of FITC-CSE: Dissolve 5 mg CSE in 1 mL of pH 8.5 carbonate buffer, add 0.5 mg FITC (pre-dissolved in 50 μL DMSO), and react at room temperature in the dark for 4 hours. After the reaction, load the mixture onto a Sephadex G-25 gel filter column pre-equilibrated with PBS, and collect the first yellow band to flow out to obtain purified FITC-CSE.

[0051] 2) Labeling and purification of TRITC-CMCS: 100 mg of CMCS was dissolved in 10 mL of deionized water, and 2 mg of TRITC (pre-dissolved in 200 μL of DMSO) was added. The mixture was stirred overnight at room temperature in the dark. The reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed in deionized water for 3 days (changing the water daily). The solution was then freeze-dried to obtain TRITC-CMCS.

[0052] 3) FRET efficiency determination: FITC-CSE and TRITC-CMCS were used to prepare SM-CSE microcapsules according to the method in Example 4. The prepared microcapsule suspensions were obtained, and the pH was adjusted to 5.5 and 6.8 respectively. After equilibration for 30 min, the emission spectra were measured at an excitation wavelength of 488 nm using a fluorescence spectrophotometer.

[0053] FRET efficiency is calculated using the following formula: E = 1 - (F DA / F D ), where F DA F represents the fluorescence intensity of the donor (FITC) in the presence of the acceptor (TRITC). D The fluorescence intensity is when the donor is present alone.

[0054] like Figure 10 As shown in Table 5, the FRET efficiency dropped sharply from 85.3% at pH 5.5 to 42.7% at pH 6.8, indicating that the donor-acceptor distance inside the microcapsules prepared in Example 4 increased and the structure became looser. This confirms that SM-CSE undergoes significant structural swelling at pH above 5.8, both at the macroscopic (particle size) and molecular (FRET) levels.

[0055] Table 5

[0056] Note: p < 0.001 compared to data at pH 5.5.

[0057] (5) Characterization of mechanical properties of single particles Appropriate amounts of the microcapsule suspensions prepared in Example 4 (SM-CSE), Comparative Example 1 (MC-CL), and Comparative Example 2 (MC-CT) were diluted with deionized water and dropped onto freshly peeled mica sheets, then dried at room temperature. Nanoindentation tests were performed using atomic force microscopy in contact mode, using a silicon nitride probe with an elastic constant of 0.06-0.12 N / m, with the indentation depth controlled at 20-50 nm and the indentation rate at 1 Hz. More than 30 microcapsules were randomly selected from each sample for testing, and the force-distance curves were recorded. The elastic modulus of the microcapsules was calculated using the Hertz model, and the maximum deformation rate at the time of microcapsule rupture was recorded.

[0058] like Figure 11-12 As shown in Table 6, the elastic modulus of SM-CSE is 4.7 times that of MC-CL and 3.3 times that of MC-CT, and it has the lowest maximum deformation rate, indicating that the sequential crosslinking strategy significantly enhances the rigidity and deformation resistance of the microcapsule wall.

[0059] Table 6

[0060] Note: p<0.001 compared with the SM-CSE group.

[0061] (6) Stability test of high pressure processing Take 5 mL of each of the microcapsule suspensions prepared in Example 4 (SM-CSE), Comparative Example 1 (MC-CL), and Comparative Example 2 (MC-CT), and place them in a high-pressure homogenizer. Cycle them three times at pressures of 500 bar, 1000 bar, and 1500 bar. Take samples before and after treatment to determine the encapsulation efficiency, particle size, and polydispersity index (PDI) of the microcapsules. The encapsulation efficiency retention rate is calculated as follows: Encapsulation efficiency retention rate (%) = (Encapsulation efficiency after treatment / Encapsulation efficiency before treatment) × 100%.

[0062] like Figure 13 As shown in Table 7, after high-pressure treatment at 1500 bar, SM-CSE still retained an encapsulation efficiency of up to 94.2%, with minimal changes in particle size and PDI.

[0063] Table 7

[0064] (7) Rheological property testing Take 2 mL of each of the microcapsule suspensions prepared in Example 4 (SM-CSE), Comparative Example 1 (MC-CL), and Comparative Example 2 (MC-CT), place them on the sample stage of the rheometer, select a 40 mm parallel plate rotor, and set the gap to 500 μm; perform dynamic frequency scanning tests at 25℃, with a scanning frequency range of 0.1-10 Hz and strain controlled within 1% (within the linear viscoelastic region), and record the storage modulus (G') and loss modulus (G'').

[0065] Rheological test results as follows Figure 14 As shown, the G' of the SM-CSE suspension was 156±11 Pa, which was significantly higher than that of the control group, indicating that the microcapsule network it formed had stronger solid properties and excellent processing tolerance.

[0066] (8) Study on in vitro release behavior Preparation of pH 5.5 release medium: Accurately weigh 0.68 g of potassium dihydrogen phosphate, 4.50 g of sodium chloride, and 0.50 g of sodium dodecyl sulfate, dissolve them in about 900 mL of deionized water, adjust the pH to 5.50 ± 0.05 with 1 M NaOH solution, and finally make up the volume to 1000 mL to obtain the pH 5.5 release medium; Preparation of pH 6.8 release medium: Accurately weigh 1.42 g of disodium hydrogen phosphate, 0.27 g of potassium dihydrogen phosphate, 4.50 g of sodium chloride, and 0.50 g of sodium dodecyl sulfate, dissolve them in about 900 mL of deionized water, adjust the pH to 6.80 ± 0.05, and finally bring the volume to 1000 mL to obtain the pH 6.8 release medium.

[0067] 2) Release experiment procedure: Take 2 mL of each of the microcapsule suspensions prepared in Example 4 (SM-CSE), Comparative Example 1 (MC-CL), and Comparative Example 2 (MC-CT) (calculated after accurate determination of CSE content), and place them into pretreated dialysis bags (MWCO 8000-14000 Da), tying both ends tightly. Place the dialysis bags in 50 mL of the pH 5.5 and pH 6.8 release media prepared above, respectively, and conduct release experiments in a constant temperature shaking water bath at 37℃ (100 rpm). Take 5 mL of release media at preset time points (0.5, 1, 2, 4, 6, 8, 12, 24, 36 h), and add an equal volume of fresh release media at the same temperature. Use high performance liquid chromatography to determine the concentration of CSE in the release media at each time point, calculate the cumulative release rate, and plot the release curve.

[0068] like Figure 15-17 As shown in Table 8, SM-CSE ( Figure 15It exhibits unique "intelligent gating" release characteristics: slow release at pH 5.5 (36h release -29%), and "delayed-accelerated" release at pH 6.8, ultimately reaching a release rate of 70.2%, an increase in release rate of 2.45 times. As a control, MC-CL ( Figure 16 ) and MC-CT ( Figure 17 The release curves of the microcapsules almost overlapped under the two pH conditions, indicating no intelligent responsiveness.

[0069] Table 8

[0070] Note: p<0.01 compared with the release rate of the same sample at pH 5.5.

[0071] (9) In vitro transdermal test 1) Skin preparation Take fresh detached pig skin (approximately 0.8-1.2 mm thick), remove subcutaneous fat tissue, rinse thoroughly with physiological saline, wrap in aluminum foil, and freeze at -20°C for later use; before the experiment, thaw naturally in physiological saline at 4°C and equilibrate for 2 hours.

[0072] 2) Transdermal absorption test In vitro transdermal experiments were conducted using a Franz vertical diffusion cell. Treated porcine skin was fixed between the supply and receiving cells, with the keratin layer facing the supply cell. The experiment consisted of four groups: a CSE solution group (using an equal volume of CSE dissolved in PBS as a control), an MC-CL group (microcapsules prepared in Comparative Example 1), an MC-CT group (microcapsules prepared in Comparative Example 2), and an SM-CSE group (microcapsules prepared in Example 4). The dosage of CSE was kept consistent across all groups (1.0 mg / cm³). 2 The receiving chamber was filled with PBS buffer (pH 6.8, containing 0.5% BSA and 0.01% NaN3 to prevent microbial growth), magnetically stirred at 400 rpm, and the temperature maintained at 32 ± 0.5℃. Samples of 0.5 mL were taken from the receiving chamber at 0.5, 1, 2, 4, 6, 8, 12, and 24 hours, and immediately replenished with an equal volume of fresh receiving solution at the same temperature. After filtration through a 0.22 μm filter, the CSE concentration was determined by HPLC at 325 nm, and the cumulative transdermal delivery was calculated.

[0073] like Figure 18 As shown, the cumulative transdermal CSE dose (Q) in the SM-CSE group over 24 hours was... 24 The concentration was 14.28 ± 0.96 μg / cm³. 2 The concentration was significantly higher than that in the CSE solution group (7.35 ± 0.72 μg / cm³). 2 ), MC-CL group (6.85±0.68 μg / cm2 ) and MC-CT group (6.62±0.64 μg / cm 2 (p<0.01).

[0074] 3) Measurement of skin retention After the transdermal test, the skin was removed, rinsed three times with physiological saline, the surface moisture was absorbed with filter paper, the skin was cut into small pieces, and 2 mL of methanol was added for homogenization and extraction. The supernatant was collected by centrifugation, and the concentration of CSE in the skin homogenate was determined by HPLC. The amount of skin retained per unit area was calculated.

[0075] like Figure 19 As shown, the skin retention amount in the SM-CSE group was 4.92±0.38 μg / cm³. 2 The CSE group (1.86 ± 0.22 μg / cm) 2 The effect was 2.65 times greater than that of the previous year (p<0.01), indicating that SM-CSE microcapsules form an effective reservoir in the skin, which is beneficial for the continuous exertion of repair effects.

[0076] 2. Verification of the efficacy of in vitro cell intelligent repair (1) Cell culture and establishment of a microenvironment model of skin barrier damage Cell culture: Human immortalized keratinocytes (HaCaT, ATCC CRL-2404) were routinely cultured and passaged in DMEM high-glucose medium containing 10% fetal bovine serum and 1% penicillin-streptomycin at 37°C, 5% CO2 and saturated humidity.

[0077] Establishment of a microenvironment model for a damaged skin barrier: The damaged model culture medium (pH 6.8) was precisely prepared. The principle was to add exogenous lactic acid to simulate the weakly acidic environment before the pH rise after skin damage. The final concentration of the target lactic acid was 10 mM.

[0078] To prepare a 100 mL system, the required mass of pure lactic acid is: 10 mmol / L × 0.1 L × 90.08 g / mol = 90.08 mg. Given that the concentration of the stock lactic acid solution is 85% (w / w), the required mass of the stock solution is: 90.08 mg ÷ 0.85 ≈ 106.0 mg.

[0079] Procedure: Accurately add 106.0 mg of 85% lactic acid solution to 100 mL of DMEM complete medium (containing 10% FBS, 1% P / S) and vortex to mix. Then, under precise pH monitoring, add 1 M NaOH solution dropwise to finely adjust the pH of the medium to 6.80 ± 0.05. The prepared medium is then filtered through a 0.22 μm filter membrane for sterilization to obtain the "damaged model medium (pH 6.8)", which should be stored at 4°C and used within one week.

[0080] Normal control medium: Conventional DMEM complete medium (without lactate, pH=7.4) was used as a control to simulate the normal skin microenvironment.

[0081] Cell seeding and model establishment: HaCaT cells in logarithmic growth phase were digested, resuspended, and counted; cells were seeded at 1×10⁻⁶ cells per cell line. 4 cells / well or 2×10 5 Cells were seeded at a density of 96-well or 6-well plates. After seeding, all cells were cultured in normal control medium at pH 7.4 for 24 hours to ensure complete cell adhesion and uniform cell condition. After 24 hours, the original medium was discarded, and the experimental group was replaced with the above-prepared damaged model medium (pH 6.8), while the control group was replaced with fresh normal control medium (pH 7.4) to establish a microenvironment model of skin barrier damage, and subsequent treatments were performed.

[0082] (2) Experimental grouping and drug administration After the cells adhered for 24 hours, the original culture medium was discarded, and the cells were washed twice with sterile PBS (pH 7.4). Subsequently, the culture medium was replaced with the appropriate pH medium, and the treatment drugs were added according to the following experimental groups: Normal control group (Ctrl-pH7.4): replaced with fresh pH 7.4 DMEM complete medium; Damaged model control group (Model-pH 6.8): replaced with a skin barrier damaged microenvironment model culture medium at pH 6.8; CSE treatment group (CSE-pH 6.8): CSE solution was added to the skin barrier damaged microenvironment model culture medium at pH 6.8 to make the final CSE concentration 10 μg / mL; SM-CSE microcapsule treatment group (SM-CSE-pH 6.8): The SM-CSE microcapsule suspension prepared in Example 4 was added to the skin barrier damaged microenvironment model culture medium at pH 6.8 and adjusted to a final concentration of CSE of 10 μg / mL. SM-CSE microcapsule control group (SM-CSE-pH 7.4): The SM-CSE microcapsule suspension prepared in Example 4 was added to DMEM complete medium at pH 7.4 and adjusted to a final concentration of CSE of 10 μg / mL. All drug solutions and microcapsule suspensions were freshly prepared using culture medium of the corresponding pH and vortexed to mix. After changing the culture medium and administering the drug, the cells were returned to the incubator for 24 hours of further culture. Each experiment was conducted in 6 replicates (n=6) and was independently repeated 3 times.

[0083] (3) Detection of cell viability and oxidative stress level Cell viability assay (CCK-8 assay): After 24 hours of treatment, 10 μL of CCK-8 reagent was added to each well of a 96-well plate, and the plates were incubated for another 2 hours. Subsequently, the absorbance (OD) of each well was measured at 450 nm using a microplate reader. 450 Cell viability (%) is calculated using the following formula: Cell viability (%) = [(OD treatment)] OD starve) / (OD sham OD starve)] × 100%; In the formula, OD treatment is the average absorbance of the treatment group, OD starve is the absorbance of the blank well containing only culture medium, and OD sham is the average absorbance of the normal control group (Ctrl-pH 7.4).

[0084] Intracellular reactive oxygen species (ROS) level detection (DCFH-DA fluorescent probe method): After treatment, the culture medium was discarded, and the cells were gently washed twice with preheated PBS. 100 μL of DCFH-DA fluorescent probe working solution diluted to 10 μM with serum-free DMEM was added to each well, and the cells were incubated at 37℃ in the dark for 30 min. After incubation, the probe solution was discarded, and the cells were washed three times with PBS to completely remove any probes that had not entered the cells. Subsequently, the fluorescence intensity of each well was immediately measured using a fluorescence microplate reader under the conditions of excitation wavelength 485 nm and emission wavelength 535 nm. The relative ROS level of each experimental group was calculated based on the average fluorescence intensity of the damaged model control group (Model-pH6.8) (100%).

[0085] (4) Barrier-related protein expression analysis (Western blot) Total protein extraction from cells: After 24 hours of treatment, wash the cells in the 6-well plates twice with pre-chilled PBS. Add 150 μL of RIPA lysis buffer containing 1% (v / v) protease inhibitor and phosphatase inhibitor to each well and lyse on ice for 30 min. Collect the lysate into pre-chilled centrifuge tubes using a cell scraper and centrifuge at 14000×g for 15 min at 4°C. Collect the supernatant as the total protein sample.

[0086] Protein concentration determination: The protein concentration of each sample was determined using the BCA protein concentration assay kit (Thermo Scientific) strictly following the instructions. Subsequent sample loading volumes were then accurately calculated based on this concentration.

[0087] SDS-PAGE electrophoresis and transfer: 30 μg of total protein was mixed with 5× Loading Buffer and heated at 100℃ for 5 min to denature the protein. The sample was loaded onto a 10% SDS-PAGE gel for electrophoresis (stacking gel at 80 V and separating gel at 120 V). After electrophoresis, the protein was transferred to a PVDF membrane using a wet transfer method at a constant current of 300 mA for 90 min.

[0088] Immunoblot: The PVDF membrane after transfer was blocked with TBST solution containing 5% (w / v) skim milk powder at room temperature for 1 hour; then, it was incubated overnight at 4°C with the following primary antibody: Rabbit anti-human filaggrin polyclonal antibody (1:1000, Abcam, ab24584). Rabbit anti-human acetoxin polyclonal antibody (1:1000, Abcam, ab85679). Mouse anti-human β-actin monoclonal antibody (1:5000, Sigma, A1978). After washing the membrane three times with TBST (10 min each time), it was incubated with the corresponding HRP-labeled goat anti-rabbit / mouse secondary antibody (1:5000) at room temperature for 1 hour, and then washed again with TBST.

[0089] Chemiluminescence and quantitative analysis: ECL chemiluminescence substrate was used for development, and images were acquired in a chemiluminescence imaging system; ImageJ software was used to analyze the gray values ​​of the target band and the β-actin internal reference band.

[0090] The relative expression level of the target protein was calculated using the formula: (target protein band gray value) / (corresponding β-actin band gray value). The final data were expressed and analyzed as the relative fold increase of each experimental group compared to the normal control group (Ctrl-pH 7.4).

[0091] like Figure 20-21 As shown in Table 9, in a damaged environment at pH 6.8, the SM-CSE-pH6.8 group showed the best cell viability recovery (89.5%) and the strongest ROS scavenging ability, with significantly better results than the CSE group, demonstrating its intelligent synergistic effect in damaged environments.

[0092] Table 9

[0093] Note: ** indicates p < 0.01 compared to the Ctrl-pH7.4 group; # indicates p < 0.01 compared to the Model-pH6.8 group; ## indicates p < 0.01 compared to the CSE-pH6.8 group.

[0094] like Figure 22-23As shown in Table 10, under pH 6.8 conditions, the expression levels of Filagrin and Loricrin proteins in the SM-CSE-pH6.8 group were 1.9 times and 1.7 times that of the CSE group, respectively, and were significantly higher than their self-expression levels under normal pH 7.4 conditions. This further confirms the intelligent characteristics of SM-CSE in "sensing the damaged state and triggering precise repair".

[0095] Table 10

[0096] 3. Animal experiments to verify (1) Establishment of experimental animal and skin injury models SPF-grade female SD rats (7-8 weeks old, weighing 180-220 g, purchased from Liaoning Changsheng Experimental Animal Technology Co., Ltd.) were selected. The rats were housed in an independent ventilation cage system (IVC) with constant temperature and humidity (22±2°C, humidity 50±10%) and 12 h / 12 ​​h light and dark cycle, and were allowed free access to food and water.

[0097] Hair removal on the back: 24 hours before the experiment, the back of the rats was shaved using an electric shaver and hair removal cream (approximately 3 cm × 4 cm area). After hair removal, the skin was immediately washed thoroughly with warm water and gently dried.

[0098] UVB irradiation damage: After 24 hours of hair removal, when the skin was confirmed to be intact, the hair-removed areas of rats were irradiated once using a calibrated UVB therapy device (peak wavelength 311nm). Referring to relevant literature on the matching of rat skin thickness with irradiation dose, this experiment used 250-350 mJ / cm². 2 The irradiation dose was determined; after irradiation, rats were housed individually, and the skin in the irradiated area was observed to show uniform moderate erythema and mild edema within 24-48 hours, indicating that the acute skin barrier injury model was successfully established.

[0099] (2) Experimental grouping and dosing regimen Experimental grouping: The experimental animals were randomly divided into the following 4 groups, with 8 animals in each group: Blank control group: Normal rats, coated with blank gel matrix; Model control group: UVB-damaged rats, coated with blank gel matrix; CSE group: UVB-damaged rats were coated with gel containing CSE; SM-CSE group: UVB-damaged rats were coated with SM-CSE smart microcapsule gel prepared in Example 4; Preparation of the blank gel matrix: 1.00 g of carbomer 940 was dispersed in 90 mL of deionized water and swollen overnight. 5.00 g of glycerol and 0.05 g of methylparaben were added. The pH was adjusted to 6.8-7.0 with triethanolamine while stirring. Water was added to a total weight of 100 g and homogenized to obtain the blank gel matrix.

[0100] Preparation of CSE-containing gel: 10 mg of CSE powder or 100 mg of SM-CSE lyophilized powder was ground and premixed with 1.0 g of glycerol, and then 98.9 g of blank gel matrix was added. The mixture was stirred under vacuum at low speed for 1 h to ensure uniform dispersion and obtain CSE-containing gel.

[0101] Administration method: At 9:00 a.m. every day, after lightly anesthetizing the rats, accurately weigh 250 mg of the corresponding gel and apply it evenly to the hair loss lesion area on the back using a medicator; after application, isolate and observe the rats in a single cage for 30 minutes to prevent drug loss. Administer once daily for 7 consecutive days.

[0102] (3) Observation and detection indicators Macroscopic skin scoring: On day 0 (24 hours after model establishment), day 3 and day 7, a double-blind assessment was conducted by two researchers who were unaware of their assigned groups; according to the modified Draize scoring criteria, three indicators, namely erythema, desquamation / scab formation and edema, were scored separately (0-3 points for each); the average of the two scores was used as the total skin damage score at each time point (maximum 9 points).

[0103] Transdermal water loss measurement: Four hours after the last administration on day 7, transdermal water loss was measured using a transdermal water loss meter in a constant temperature and humidity chamber (22±1℃, 50±5% RH). The probe was gently placed in the center of the damaged area, and after the reading stabilized, five stable values ​​were recorded and averaged. The results are expressed as g / (h·m). 2 )express.

[0104] Tissue sample collection and processing: After TEWL measurement, rats were anesthetized and euthanized. Full-thickness skin tissue (approximately 1 cm × 1 cm) from the central area of ​​the injury was aseptically excised, flash-frozen in liquid nitrogen, and stored at -80°C for protein analysis.

[0105] Detection of skin barrier-related protein expression: Approximately 50 mg of frozen skin tissue was taken, homogenized in liquid nitrogen, and then 1 mL of RIPA lysis buffer containing protease inhibitors was added for homogenization on ice. After centrifugation, the supernatant was collected and analyzed using a BCA protein concentration assay kit (Thermo Scientific).

[0106] SDS-PAGE electrophoresis and transfer: 30 μg of total protein was mixed with 5× Loading Buffer and denatured at 100℃ for 5 minutes; the sample was loaded onto a 10% SDS-PAGE gel for electrophoresis (stacking gel constant voltage 80 V, separating gel constant voltage 120 V); after electrophoresis, the protein was transferred to a PVDF membrane using the wet transfer method at a constant current of 300 mA for 90 minutes. The primary antibodies used and their dilution ratios are as follows: rabbit anti-mouse Filaggrin polyclonal antibody (1:1000, Proteintech, 10834-1-AP), rabbit anti-mouse Loricrin polyclonal antibody (1:1000, Proteintech, 17448-1-AP), and mouse anti-β-actin monoclonal antibody (1:5000, Sigma, A1978).

[0107] like Figure 24 As shown, the skin erythema, desquamation, and edema in the SM-CSE treatment group have basically subsided.

[0108] Skin lesion scoring results, such as Figure 25 As shown in Table 11, on day 7 of treatment, the skin damage score (1.8±0.5) and transepidermal water loss value (11.3±1.9 g / h·m) in the SM-CSE group were... 2 Both were significantly lower than the model control group (6.8±0.9 and 28.5±3.2 g / h·m, respectively). 2 The levels in the CSE group and the CSE group were 4.1±0.7 and 18.7±2.4 g / h·m, respectively. 2 The levels were close to those of the blank control group (0.0±0.0 and 8.2±1.5 g / h·m, respectively). 2 This demonstrates its remarkable barrier repair effect at the macro level.

[0109] Table 11

[0110] Note: Compared with the blank control group, p<0.01; compared with the model control group, p<0.01; compared with the CSE group, p<0.01.

[0111] Quantitative statistical results of epidermal thickness are as follows: Figure 26 As shown in Table 12, the epidermal thickness of the SM-CSE treatment group was significantly lower than that of the model control group and the CSE group, indicating that it can effectively repair the ultrastructure of damaged skin.

[0112] Table 12

[0113] Barrier protein expression analysis results, such as Figure 27-28As shown, the relative expression levels of Filagrin and Loricrin proteins in the SM-CSE treatment group were significantly higher than those in the model control group and the CSE group, indicating that it can significantly upregulate the expression of key barrier proteins at the molecular level and promote barrier repair.

[0114] The specific embodiments of the present invention disclosed above are merely illustrative of the invention. These embodiments do not exhaustively describe all details, nor do they limit the invention to the specific embodiments described. Many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.

Claims

1. A method for preparing sea fennel composite intelligent microcapsules based on sequential cross-linking, characterized in that, The preparation method includes the following steps: S1: Weigh out sea fennel extract CSE and dissolve it in lactate-sodium lactate buffer solution at pH 4.

80. Vortex the solution until it is completely dissolved. Filter the solution through a 0.22 μm aqueous filter membrane to obtain CSE stock solution. Store at 4°C in the dark. S2: Weigh carboxymethyl chitosan and dissolve it in a lactate-sodium lactate buffer solution at pH 5.

20. Stir overnight until completely dissolved to obtain a carboxymethyl chitosan solution. Weigh sodium tripolyphosphate and dissolve it in deionized water. Stir at 800 rpm to obtain a sodium tripolyphosphate solution. Add the sodium tripolyphosphate solution dropwise to the carboxymethyl chitosan solution at a rate of 1 mL / min. Continue stirring for 30 min to carry out the pre-crosslinking reaction. Finally, make up the volume with a lactate-sodium lactate buffer solution at pH 5.20 and filter through a 0.45 μm filter membrane to obtain a pre-crosslinking solution containing carboxymethyl chitosan and sodium tripolyphosphate. S3: The CSE stock solution prepared in S1 is used as phase A, and the pre-crosslinked solution prepared in S2 is used as phase B. The phase A and phase B solutions are respectively loaded into two independent syringes with precision injection pumps. The phase A and phase B solutions are introduced into the Inlet A and Inlet B of the microfluidic chip through polytetrafluoroethylene tubes, respectively. Under laminar flow conditions, the fluid turns multiple times through the serpentine channel and achieves gentle layer-by-layer encapsulation by interfacial diffusion. The opalescent suspension is collected from the microfluidic chip outlet and aged at 25°C for 30 min to obtain the primary microcapsule suspension. S4: Under magnetic stirring conditions of 25 ± 1°C and 500 rpm, the LA stock solution was added dropwise to the primary microcapsule suspension prepared in S3. After the addition was complete, stirring was continued for 30 min to obtain the LA-functionalized microcapsule suspension. The LA stock solution was prepared by weighing 3.00 g of lactobionic acid and dissolving it in 10 mL of lactate-sodium lactate buffer solution with pH 4.

80. The solution was then vortexed to obtain an LA stock solution with a concentration of 30% w / v. The mixing volume ratio of the primary microcapsule suspension to the LA stock solution was 143:

1. S5: The LA-functionalized microcapsule suspension from S4 was placed in an ITC sample cell and heated to 45°C. Under continuous stirring, the SGE working solution was titrated using ITC monitoring until the system heat flow signal stabilized and returned to the baseline, indicating that the covalent cross-linking reaction was nearing completion, thus obtaining sea fennel composite intelligent microcapsules. Preparation method of SGE working solution: Take 200 μL of 3-glycidyl etheroxypropyltrimethoxysilane stock solution, add 800 μL of anhydrous ethanol and 100 μL of 0.1 M hydrochloric acid, vortex mix, and let stand at room temperature for hydrolysis for 30 min; then, dilute it with lactate-sodium lactate buffer at pH 4.80 and bring the volume to 10 mL to obtain a 20 mM SGE working solution.

2. The preparation method according to claim 1, characterized in that, The preparation method of the lactate-sodium lactate buffer solution described in S1 is as follows: Weigh 0.42 g of lactic acid and 0.58 g of sodium lactate, dissolve them in 100 mL of deionized water, and adjust the pH to 4.

80.

3. The preparation method according to claim 1, characterized in that, The concentration of the CSE stock solution described in S1 is 1.0% w / v.

4. The preparation method according to claim 1, characterized in that, The mass-to-volume ratio of the sea fennel extract to the lactate-sodium lactate buffer solution in S1 is 10 mg: 1 mL.

5. The preparation method according to claim 1, characterized in that, The concentration of the carboxymethyl chitosan solution in S2 is 3.0%; the concentration of the sodium tripolyphosphate solution is 0.3%; and the mass ratio of the sodium tripolyphosphate to the carboxymethyl chitosan is 1:

10.

6. The preparation method according to claim 1, characterized in that, The flow rates of phase A and phase B solutions introduced into the microfluidic chip via polytetrafluoroethylene tubes in S3 are 15 μL / min and 10 μL / min, respectively.

7. A sea fennel composite intelligent microcapsule based on sequential cross-linking, characterized in that, The sea fennel composite intelligent microcapsules are obtained by the preparation method described in any one of claims 1 to 6.

8. The application of the sea fennel composite intelligent microcapsules according to claim 7 in the preparation of tissue repair materials or cosmetics.

9. The application of the sea fennel composite intelligent microcapsules according to claim 7 in the preparation of regenerative medicine materials.

Citation Information

Patent Citations

  • Preparation method and application of water-soluble chitosan nanoparticle-temperature-sensitive hydrogel compound

    CN114848583A

  • Crithmum maritimum composition as well as preparation process and use method thereof

    CN115990129A